Weed interference and control in white yam (Dioscorea rotundata Poir) - Akobundu, I.O. (Wiley, 1981)
The climbing growth habit of white yam (Dioscorea rotundata) coupled with its inability to shade the ground completely at any stage of its growth and development makes it very susceptible to weed interference. The critical period of weed interference in white yam was between the 8th and 16th week after planting (w.a.p.) for yam planted at the onset of rains. Keeping yam plants weedy for 16 w.a.p. or beyond significantly reduced tuber yield; keeping them weed‐free for the same period resulted in a significant increase in tuber yield. A minimum of three weedings within 16 w.a.p. are necessary to minimize yield reduction caused by weeds. The lowest weed weight and highest crop yield from herbicide treatments were obtained where a mixture of fluometuron and metolachlor each at 2.0 kg a.i./ha was used for pre‐emergence weed control.